Передвижная электрофизическая установка ГИТ-20 для электроимпульсной обработки шламов металлургического производства - Коляда, Ю.Е.; Доценко, В.И.; Недзельский, О.С.; Пличко, А.В.; Понуждаева, Е.Г. (Електротехніка і електромеханіка, 2011)
The paper presents results of engineering development of a powerful mobile electrophysical installation "GIT-20" designed for technological processing of sludge of metal manufacture through electric hydraulic effects caused by pulsed discharge currents. Results of experimental studies of characteristics of voltage pulses initiating a guaranteed discharge of a current pulse generator in real-world technological environment are given.